Students' perception of total quality management: role of location and gender. (13th April 2015) - Pourrajab, Masoumeh; Basri, Ramli; Daud, Shaffe Mohd; Asimiran, Soaib Bin
The aim of this study is to identify the level of Total Quality Management (TQM) as practiced by secondary schools in Lorestan province, Iran, based on students' perception. Additionally, the paper aims to investigate the relationship between the level of TQM and students' location and gender. To achieve these aims, the researchers conducted a survey research among 400 secondary school students. The findings of this study show that the level of TQM is medium as rated by students, and also there are significant difference between TQM's level and students' gender and location. The paper presents evidence to principals and teachers of the value of implementing TQM principles in schools to increase students' satisfaction.